2019
DOI: 10.1186/s12885-019-6431-5
|View full text |Cite
|
Sign up to set email alerts
|

Are hypothalamic- pituitary (HP) axis deficiencies after whole brain radiotherapy (WBRT) of relevance for adult cancer patients? – a systematic review of the literature

Abstract: BackgroundCranial radiotherapy (cRT) can induce hormonal deficiencies as a consequence of significant doses to the hypothalamic-pituitary (HP) axis. In contrast to profound endocrinological follow-up data from survivors of childhood cancer treated with cRT, little knowledge exists for adult cancer patients.MethodsA systematic search of the literature was conducted using the PubMed database and the Cochrane library offering the basis for our debate of the relevance of HP axis impairment after cRT in adult cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Functional endocrine deficiencies after brain radiotherapy are common [23]. Long term follow-up studies indicate that radiation induced HT-P dysfunction may occur in up to 80% of patients and is often associated with an adverse impact on growth, body image, skeletal health, fertility, sexual function and physical and psychological health [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional endocrine deficiencies after brain radiotherapy are common [23]. Long term follow-up studies indicate that radiation induced HT-P dysfunction may occur in up to 80% of patients and is often associated with an adverse impact on growth, body image, skeletal health, fertility, sexual function and physical and psychological health [24].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, most data of radiation induced endocrine sequelae in adults originate from patients being treated for head and neck cancer and non-pituitary brain tumors. Endocrine follow-up data on hormonal changes after WBRT are scarce [23].…”
Section: Discussionmentioning
confidence: 99%
“…For decades,whole brain radiotherapy (WBRT) and stereotactic radiosurgery (SRS) to control neurologic symptoms and intracranial tumor growth has become a standard treatment procedure for BMs patients [8,9]. However, WBRT is usually accompanied by potential toxicity while SRS alone treatment of BMs causes a higher recurrence rate [10][11][12]. Therefore, the lack of accurate assessment methods for RT response and radiation-induced brain injury limits local control.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these symptoms are closely related to alterations of the hypothalamic function. Moreover, it has been observed that endocrine disruption of the hypothalamic-pituitary-adrenal (HPA) axis can frequently appear after WBI [12]. The hypothalamus is a region that controls many critical homeostatic functions, including those that are perturbed after whole-brain radiotherapy [12,13].…”
Section: Introductionmentioning
confidence: 99%